Incentives to Eat Healthily: Evidence from a Grocery Store Field Experiment. (17th December 2021) - List, John A.; Samek, Anya; Zhu, Terri
Abstract : We use a field experiment with over 200 participants to investigate the effect of incentives on grocery store purchases. We randomize participants to treatments where we incentivize produce purchases, provide tips for produce preparation, or both, and follow shopping behaviour for 6 months. Our informational treatment has a weak effect. However, we find an important price effect: modest incentives quadruple produce purchasing at our grocery store relative to the control group. After incentives are removed, the treatment group continues to purchase more produce at our grocery store. These long‐term results are consonant with a habit‐formation model, in contrast to standard price models or behavioural 'crowd out' models.